Arganiella Giusti & Pezzoli, 1980 (Caenogastropoda: Truncatelloidea: Hydrobiidae): a widespread genus or several narrow-range endemic genera? - Delicado, Diana; Pešić, Vladimir; Ramos, Marian A. (European Journal of Taxonomy, 2021)
Most valvatiform genera of the gastropod family Hydrobiidae are narrow-range taxa. One exception is the genus Arganiella, which is comprised of three congeners: the type species A. pescei from the Apennine Peninsula, A. wolfi from the Iberian Peninsula and A. tabanensis from the Balkans. The genus assignment of the latter two species was based on morphological similarities with A. pescei in the shell, operculum, radula and genitalia. Given that the morphology of hydrobiids is sometimes susceptible to convergence, this study re-evaluates the taxonomic status of species of Arganiella by analysing mitochondrial (mtCOI) and nuclear (18S rRNA) sequences of topotypes or near topotypes to infer their phylogenetic position. Our phylogenetic analyses depicted Arganiella as a non-monophyletic group within Hydrobiidae, and sequence divergence among the three species ranged from 14.5 to 16.7% for mtCOI and 2.0 to 3.8% for 18S. We also re-examined the extent of morphological variation among species of Arganiella and found a few differences among them and other valvatiform genera. Consequently, we propose two new genera for A. wolfi and A. tabanensis. Our results conflict with the classification of valvatiform hydrobiid species solely based on traditional phenotypical methods and suggest further taxonomic evaluation within a molecular framework.